Sensitive voltammetric method for the fast analysis of the Sunagreen using a boron doped diamond electrode - Chýlková, Jaromíra; Tomášková, Markéta; Jehlička, Vladimír; Šelešovská, Renáta; Hlavatá, Petra (BEST Servis, 2016)
A voltammetric method has been developed for the determination of a mixture of 2−aminobenzoic acid and 2−hydroxybenzoic acid that both are present in the Sunagreen fortmulation used as a plants growth stimulator. After opzimization of the key experimental and instrumental conditions, linear sweep voltammetry mode was chosen to determine both main substances and combined with a boron-doped diamond electrode in the role of convenient working electrode. Specially, in this work, a new mathematical algorithm was proposed serving to evaluate the respective voltammetric current signals that had originally been nonlinear with concentration. Limits of detection (LODs) for 2-aminobenzoic acid and 2-hydroxybenzoic acid were estimated to be 5.24 mol L-1 and 7.0 mol L-1, resp. Finally, selected real samples were anaylyzed and the results obtained agreed well with the declared values.
Voltametrická metoda stanovení nízkých koncentrací Sunagreenu pomocí BDDE
Keywords: voltammetry; plant growth sunagreen; BDDE; voltametrie; sunagreen; BDDE